Penerapan Model Pembelajaran Discovery Learning Strategi Think Talk Write Dalam Meningkatkan Motivasi Dan Hasil Belajar Menulis Teks Ulasan Kelas VIII SMP - Dewi Adeninawaty; Rahmat Soe’oed; Ahmad Ridhani (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2018)
This study aims to determine (1) teacher teaching activities in applying Discovery Learning Think Talk Write (DL-TTW) learning models, (2) student learning activities in implementing the Discovery Learning Think Talk Write (DL-TTW) model, (3) increased motivation to learn to write text on student reviews in applying the Discovery Learning Think Talk Write (DL-TTW) Learning model, (4) improvement of learning outcomes writing text review in the application of the Discovery Learning Think Talk Write (DL-TTW) learning model. This research is a classroom action research with four stages including: planning, action, observation and reflection. The subjects of this study were VIII B students of Al-Muhajirin Middle School in Muara Badak Kab. Kutai Kertanegara 2017/2018 school year, totaling 28 students. Data collection techniques used are observation, documentation, interviews, field notes and tests.Data validity in this study uses data source triangulation and method triangulation. The data analysis technique used is an interactive analysis model developed by Miles and Huberman which consists of four components, namely data collection, data reduction, data presentation, and conclusion drawing. The results of the study are 1) teacher teaching activities have increased by an average of 64.71% in cycle I and an average of 87.25% in cycle II, 2) student learning activities have increased with an average of 54.44% in cycle I and an average of 84.44% in cycle II, 3) student learning motivation has increased by an average of 53.83% in cycle I and an average of 84.19% in cycle II, 4) student learning outcomes have increased with an average of 52.38% in cycle I and an average of 84.52% in cycle II. It can be concluded that the implementation of the model with this learning strategy has increased.